Influência do ambiente e da conectividade espacial nos componentes α e β da diversidade funcional em assembleias de peixes do alto rio Paraná. - Peláez Zapata, Oscar Eduardo (2016)
Distribution and coexistence of species is determined by mechanism operating at different spatial and temporal scales. Traits diversity in an assemblage can be driven by environmental selection, species dispersal and competitive abilities and stochastic processes. Here, we aimed to evaluate the effects of spatial and environmental components on functional α and β diversity in fish assemblies. Alpha functional diversity assessed the functional space occupied by species (functional richness), the degree of dispersion or functional space occupation by species (functional dispersion) and originality of traits in each assembly (functional originality). Functional divergence between assemblies, functional beta diversity, was decomposed into functional turnover and functional nestedness. A spatial model was used like a proxy of assemblies connectivity. Posteriorly, correlation between functional traits and environmental variables was assessed. Spatial variables explained a higher proportion of functional diversity variation. Functional β diversity was higher than taxonomic β diversity and its variation was explained by both, spatial and environmental components. Significant relation of alpha and beta functional diversity with spatial component suggest that different mechanism, at different spatial scales and zones of the studied region, can lead to observed pattern. Including a descriptor of spatial connectivity extent and direction, allowed determined that at local scale functional diversity was influenced by connectivity extent, and at large spatial scales both, spatial connectivity and environmental heterogeneity account for the observed pattern. These results suggest that spatial connectivity and process driven spatial connectivity could be determinant for functional diversity patterns in the studied system.